2015
DOI: 10.1188/15.cjon.e15-e20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurse Navigation on Patient Care Satisfaction and Distress Associated With Breast Biopsy

Abstract: Navigated women had lower scores on every distress measure and were less likely to seek information from an outside source. Women who were more satisfied with their care reported decreased distress; the factors influencing distress varied depending on whether they were the recipient of navigation services. In the non-navigated population, general satisfaction with care and accessibility were more likely to influence distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Based on criteria of the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies [20], methodological quality of eight studies in this systematic review ranged from weak to strong. Two studies were rated as strong [25,26], two were rated as moderate [24,27], and four were rated as weak quality (Table 2) [22,23,28,29]. One study [30] was not rated for methodological quality because it pooled data from eight other studies, making it impossible to provide specific data required to rate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on criteria of the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies [20], methodological quality of eight studies in this systematic review ranged from weak to strong. Two studies were rated as strong [25,26], two were rated as moderate [24,27], and four were rated as weak quality (Table 2) [22,23,28,29]. One study [30] was not rated for methodological quality because it pooled data from eight other studies, making it impossible to provide specific data required to rate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the three studies that found PN was associated with higher satisfaction had quality ratings of “weak” [28], “moderate” [24], and “strong” [25]. The other five studies which found no relationship between patient satisfaction and PN were also rated as “weak” [22,23,29], “moderate” [27], and “strong” [26]. Multiple studies displayed weak ratings related to selection bias, handling of confounders, data collection methods, and tracking of withdrawals and dropouts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that patients who received PN had higher satisfaction than those who did not receive PN, 10,15 whereas 2 other studies did not find a difference in satisfaction with care between those who received PN and those who did not. [11][12][13][14] This discrepancy may be related to variations in the patient navigators' technical skills and the interpersonal relationship between the patient and the patient navigator. Satisfaction with the interpersonal aspects of health care is a key component of patient satisfaction with cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are relatively few well‐designed studies evaluating whether PN is associated with higher patient satisfaction with cancer care. Four known studies have evaluated whether patients receiving PN were more satisfied with care by comparing these individuals with patients who did not receive PN or by comparing patients' ratings of satisfaction before and after participation in a PN intervention . The results of these studies are mixed.…”
Section: Introductionmentioning
confidence: 99%